Research and application practice of China Telecom in all-optical network - Jianjun TANG; Junjie LI; Chengliang ZHANG (Dianxin kexue)
With the advancement of national strategies such as “Broadband China” and “Speed-up and Fee-reduction”,network traffic is growing rapidly.The pressures of the space and the power supply in many equipment building of telecommunication operators are huge.All-optical network technology will effectively alleviate these pressures.Based on the analysis of the concept and connotation of all-optical network,the application value and practice of all-optical network were discussed.And the problems faced by the current all-optical network were analyzed and the future development of technology was forecasted.